2000
DOI: 10.1590/s1415-47572000000300013
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype, constitutive heterochromatin and nucleolar organizer regions (NORs) in Belosacris coccineipes (Acrididae-Leptysminae)

Abstract: Several techniques including C-banding, fluorochromes and silver staining were used to obtain information about heterochromatin patterns in the grasshopper B. coccineipes. Conventional staining showed a karyotype with 2n = 23 chromosomes in males and 2n = 24 in females, as well as XO:XX sex determination and acrotelocentric chromosomes. The medium-sized X chromosome was heteropycnotic positive at the beginning of prophase I and negative in metaphase I. C-banding revealed heterochromatic blocks in the pericentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 20 publications
(27 reference statements)
8
18
0
Order By: Relevance
“…Thus, these results have shown that the NORs in N. cruentata possess DNA rich in GC base sequences and poor in AT base sequences. NORs are known to possess GC-rich DNA in several plants (Schweizer, 1976), invertebrates (Schweizer et al, 1983;LopezFernandez et al, 1989;Loreto & Souza, 2000), and vertebrates species (Schmid, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results have shown that the NORs in N. cruentata possess DNA rich in GC base sequences and poor in AT base sequences. NORs are known to possess GC-rich DNA in several plants (Schweizer, 1976), invertebrates (Schweizer et al, 1983;LopezFernandez et al, 1989;Loreto & Souza, 2000), and vertebrates species (Schmid, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…CMA3+ bands and NORs are quite often associated with each other in insects, especially grasshoppers (e.g. Loreto & Souza, 2010) and katydids (Warchałowska-Śliwa et al, 2009). In comparison with Ephippigerini, heterochromatin in Bradyporini shows a different composition; in this case, the C-blocks were CMA3+/DAPI+, carrying both AT-and CG-rich segments.…”
Section: Cytogenetic Characterization Distribution Of Heterochromatinmentioning
confidence: 99%
“…Leptysminae, in turn, occurs only in the neotropical region and chromosomal studies of this subfamily are scarce, most of them involving standard staining (MESA et al 1982). Among the 22 Leptysminae species studied, 19 showed basic 2n=23,XO karyotypes (MESA et al 1982;MESA and FONTANETTI 1983;BIDAU and HASSON 1984;CONFALONIERI and BIDAU 1986;COLOMBO 1989;LORETO and SOUZA 2000). However, Stenopola pallida, Leptysma argentina (21,XO) and Tetrataenia surinama (19,XO) presented karyotypic reductions due to centric autosomal fusions (MESA et al 1982;BIDAU and HASSON 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The Tetrataeniini tribe, in turn, comprises 14 genera and occurs from the south of Mexico to the south of the temperate zone in Uruguay and Argentina (ROBERTS 1978;ROBERTS and CARBONELL 1980). Literature data show that most Leptysminae species have a basic karyotype of the 23,XO type in males (MESA et al 1982;MESA and FONTANETTI 1983;BIDAU and HASSON 1984;CONFALONIERI and BIDAU 1986;COLOMBO 1997;LORETO and SOUZA 2000). On the other hand, the occurrence of derived karyotypes is not frequent in this subfamily.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation